MODEL PENGELOLAAN SUMBERDAYA MANUSIA BERBASIS KOMPETENSI ERA INDUSTRI 4.0: COMPETENCY-BASED HUMAN RESOURCE MANAGEMENT MODEL IN THE INDUSTRIAL ERA 4.0 - Nopi Hidayat; Musa Hubeis; Anggraini Sukmawati; Eriyatno Eriyatno (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The symptoms caused by the existence of industry 4.0 indirectly encourage or force the organization to prioritize human resource management (Human Resource Management) so that it can last a long time and develop more advanced. This research was conducted to build a design model of competency-based human resource management across generations of the industrial era 4.0 using a soft system method. Generational differences that have been considered problems, are seen differently when the differences in the characteristics of the three generations (baby boomers, X and Y) are used as opportunities and complementary strengths in the challenges of the industrial world 4.0. In the current competency-based human resource management there are some gaps. The competency-based human resource management model across generations of 4.0 provides strategic steps taken in managing human resources. Keywords: generation, human resource management model, industry 4.0, soft sytem method